Penilaian Interaktif Berbasis Gimkit dalam IPAS Sekolah Dasar: Meningkatkan Minat Belajar dan Hasil Belajar Siswa - Rahayu, Fuji; Hariyani, Mimi (Journal of Practice Learning and Educational Development, 2026)
This study focuses on the development and testing of the use of the Gimkit platform as an interactive evaluation medium in Natural and Social Sciences (IPAS) learning to increase learning interest and learning outcomes of fifth-grade elementary school students. The method used is Research and Development (R&D) with stages of needs analysis, product design, development, validation, testing, revision, and product refinement. The research subjects included fifth-grade students at Al Azhar 54 Islamic Elementary School in Pekanbaru and their IPAS teachers. Data collection was conducted through observation, interviews, learning interest questionnaires, and learning outcome tests (pre-test and post-test), supplemented by feasibility assessments by experts. The data were analyzed descriptively, quantitatively, and qualitatively, and their effectiveness was reviewed by comparing the results before and after using the product. The results showed that Gimkit can be used as a more interesting alternative for evaluation, encouraging active student involvement and helping teachers carry out more varied assessments. In general, Gimkit-based evaluation media are considered feasible, practical, and effective for application in IPAS learning evaluation in elementary schools, and have the potential to support digital learning innovation in the era of educational transformation.